Concentration-induced structural transition of block polymer self-assemblies on a nanoparticle surface: computer simulation. Issue 104 (26th October 2016) - Xiang, Wenjun; Zhu, Zhaoju; Song, Xianyu; Zhong, Cheng; Wang, Chengjie; Ma, Yongzhang
Abstract : Film structure of asymmetric triblock copolymers assembled on different degrees of hydrophobic NP surfaces was controlled by concentration. Abstract : Coarse-grained molecular dynamic simulation (CGMD) techniques are used to study the self-assembly behavior of Pluronic triblock copolymers on different hydrophobicity nanoparticle (NP) surfaces. The structural changeover as a function of concentration of Pluronic triblock copolymers is investigated. At lower concentration ( e.g. 5%), a shell-layered film structure self-assembled on NP surfaces is observed. Above 5%, the stretching growth of polymer chains takes place during the adsorption process and the star-shaped film on NP surfaces is formed. As the simulation results show, the radius of gyration of F127 assembled on the NPs would increase with increase of polymer concentration. A transition from incomplete to complete stretching polymer chain structure growth in solvent is encountered with increasing concentrations, which appears as a high phase separation film in terms of order parameter. These changes of the self-assembled films are not majorly initiated by the hydrophobic degrees of NP surfaces, but originate from the domination of polymer concentration.